Efektivitas Aplikasi Beberapa Macam Pupuk Organik Dibandingkan Dengan Pupuk Anorganik Terhadap Pertumbuhan dan Kandungan Klorofil Tanaman Kailan (Brassica oleraceae var. alboglabra) - adinda widya rahmawati; Nurhidayati Nurhidayati; Novi Arfarita (AGRONISMA, 2022)
Kailan cultivation is generally done by farmers using inorganic fertilizers. This kind of farming system in the long term is detrimental to farmers because the soil will become infertile, the quantity and quality of vegetables will decrease. This study aims to compare the effect of using several kinds of organic fertilizers compared to inorganic fertilizers on the growth of kailan plants. This study used a Simple Randomized Block Design (RBD). There were 7 kinds of treatments, including: P0 = No fertilizer application, P1 = NPK fertilizer 4.5 g/pot, P2 = Compost fertilizer 218 g/pot, P3 = Cow dung fertilizer 397 g/pot, P4 = Chicken manure fertilizer 111 g /pot, P5 = Vermicompost fertilizer 511 g/pot, and P6 = Vermicompost powder fertilizer 147 g/pot. The dose of organic fertilizer applied is equivalent to the N content in NPK fertilizer and converted to the water content of the organic fertilizer. The variables observed included: plant height, number of leaves, leaf area and chlorophyll content. The data collected were analyzed for variance (F test) with a level of 5% to determine the effect of treatment. If the results of the F test have a significant effect, then continue with the further LSD test with a level of 5% to determine the effect of growth on plant yields. The results of this study indicate that at the end of the observation of plant growth (plant height and leaf area) the best was found in the vermicompost treatment, while the number of leaves of inorganic fertilizer, compost, vermicompost and vermicompost powder gave the same number of leaves. However, when viewed from the level of green leaf color (chlorophyll content) as measured by using a SPAD meter, vermicompost powder gave the highest chlorophyll content.Â Keywords : Kailan, Fertilizer, Growth response